Significance of determination of acrylamide monomer in anionic polyacrylamide used for treatment of water intended for human consumption - Djordjević, Marija; Stanković, Marija; Stanisavljev, Ana; Tadić, Marinela (Archives of Pharmacy, 2022)
The aim of this work is safety assessment of anionic polyacrylamide samples used as flocculants for treatment of water intended for human consumption, from the aspect of residual acrylamide monomer content, which is mandatory analysis before their entry into the water treatment plants. The safety assessment is defined by SRPS EN 1407:2011(EN 1407: 2008) - Chemicals used for treatment of water intended for human consumption - Anionic and non-ionic polyacrylamides. The main mechanism of acrylamide toxicity is oxidative stress. Its neurotoxic effects have been demonstrated in humans, while reproductive toxicity, genotoxicity and carcinogenicity have only been demonstrated in animals. The reference method for determination of acrylamide monomers is defined by SRPS EN 1407:2011, which sets the criteria for the maximum allowable concentration, which is 200 mg/kg in finished product. Test involves acrylamide monomer extraction with a mixture of methanol/water (80/20) and its determination by HPLC on a Synergy Polar-RP 4 mm 3.0x150mm column, P.N.00F-4336-Y0, Phenomenex, USA; Flow: 0.4 mL/min; Mobile phase: water: acetonitrile (96:4). Permanent analysis of anionic polyacrylamide samples before their use in water treatment plants showed good quality of these products. Only two samples in the last eleven years were defective due to increased content of acrylamide monomer, but their use due to rules of official control have been prevented. Control of residual acrylamide monomer in samples of flocculants is necessary in order not to exceed the maximum allowable concentration of acrylamide in drinking water defined by the “Rulebook on the hygiene of drinking water”, which is 0.25µg/L.